The effects of secondary tasks in semi-automated vehicles - Sundmark, Jonas; Wassén, Erik (My University, 2019)
Abstract Every year, over 1.3 million people die in the traffic. It is estimated that over 90% of these accidents are caused by human errors. Semi-automated cars looks to be the solution to lower these deaths. The goal of this master thesis work has been to look at how to make an autonomous car more attractive, specifically what would be required for a driver to conduct work in these upcoming cars. It is theorised that, if work could be safely conducted in a semi-autonomous vehicle, the increased price tag would be justified by the added value of using time for work that was previously wasted. This study tested two different ways of conducting work in the car with a passive task serving as a base line. A simulation was conducted with 15 participants to try out the three different car setups. The different setups were, a heads-up display for working tasks, a cell phone for working tasks, and a relaxation task as a base line. During each task a take-over request was presented and the response time for the take-over was gathered. After the results had been analysed it was discovered that the heads-up display showed the best result with a statistical significance compared to the cell phone task. It is theorised that the main reasoning for these results were that the system shutdown the display when the take-over request started, as well as the incentives gaze towards the road centre. This result suggests that it is not only possible to conduct work in a car, but if done right, it might even improve the cognitive recall time which could improve the re-take control of the car. Therefore, it is recommended to conduct further research within the area of using the car system to conduct work in autonomous vehicles. Keywords:
Keywords: Annan teknik; Innovation och entreprenörskap (nyttiggörande); Produktion; Other Engineering and Technologies; Innovation & Entrepreneurship; Production